Intensifying drought eliminates the expected benefits of elevated carbon dioxide for soybean - Gray, Sharon B.; Dermody, Orla; Klein, Stephanie P.; Locke, Anna M.; McGrath, Justin M.; Paul, Rachel E.; Rosenthal, David M.; Ruiz-Vera, Ursula M.; Siebers, Matthew H.; Strellner, Reid; Ainsworth, Elizabeth A.; Bernacchi, Carl J.; et al. (Nature plants, 2016)
Stimulation of C 3 crop yield by rising concentrations of atmospheric carbon dioxide ([CO 2 ]) is widely expected to counteract crop losses that are due to greater drought this century. But these expectations come from sparse field trials that have been biased towards mesic growth conditions. This eight-year study used precipitation manipulation and year-to-year variation in weather conditions at a unique open-air field facility to show that the stimulation of soybean yield by elevated [CO 2 ] diminished to zero as drought intensified. Contrary to the prevalent expectation in the literature, rising [CO 2 ] did not counteract the effect of strong drought on photosynthesis and yield because elevated [CO 2 ] interacted with drought to modify stomatal function and canopy energy balance. This new insight from field experimentation under hot and dry conditions, which will become increasingly prevalent in the coming decades, highlights the likelihood of negative impacts from interacting global change factors on a key global commodity crop in its primary region of production. The predicted rise in CO 2 levels during this century is expected to stimulate crop yields, offsetting losses from greater drought. But this study, using free-air CO 2 enrichment, shows soybean yield gains dropping to zero as drought stress increased.